Factors That Related with Incomplete Children Immunization in Kuala Tungkal II Health Center - yundri yundri; Mexitalia Setiawati; Suhartono Suhartono; Henry Setyawan; Kamilah Budhi (Universitas Airlangga, 2017)
ABSTRACT Immunization is a program be done to protect a human body from diseases. In Tanjung Jabung Barat District, the completeness of mmunization has not reached in MDGs (> 93%). According to the health agency information, showed that the completeness of  immunization in West Tanjung Tabung regency (89%) and Kuala Tungkal II health Center (78%). The purpose of this research is to analyze factors that related with the status of basic Immunization. The type of research is qualitative method through indepth interview. This research uses cross sectional design. The research was be located on Kuala Tungkal II PHC in Tanjung Jabung Barat Regency. The population is all mothers who have children aged 12-24 months. Sampling is done by random sampling. The result showed that were a significant relationship between maternal education level (p = 0.007; OR 3.15; 95% CI 1.33-7.49), mother's knowledge (p = 0.000; OR = 45.25; 95% CI 13.23-154.72), mother's attitude (p = 0.000; OR = 94.55; 95% CI 22.13-403.87), and mother's motivate  (p = 0.000;  OR= 37.00 ; 95% CI 11.40-119.99) related to the child immunization status. It can be concluded that three variables have related to incomplete immunization. It is suggested that the health agency should improve the knowledge of health personnel in training that involves the basic immunization., so as to provide education to the public about the importance of complete basic immunization. Keywords: immunization, motivate, knowledge, attitude